Exploring the association between unintended pregnancies and unmet contraceptive needs among Ugandan women of reproductive age: an analysis of the 2016 Uganda demographic and health survey - Asrat, Daniel; Copas, Andrew; Olubukola, Adesina (BioMed Central Ltd, 2024)
Abstract Unintended pregnancy and unmet contraceptive needs pose significant public health challenges, particularly in developing nations, where they contribute to maternal health risks. While previous research has explored determinants of unintended pregnancies, there remains a gap in understanding the association between unplanned pregnancies and unmet contraceptive needs among Ugandan women of reproductive age. This study aimed to assess unmet contraceptive needs and their correlation with unintended pregnancies and other factors in Uganda, utilizing a nationally representative sample. Data was extracted from the 2016 Uganda Demographic Health Survey (UDHS), a cross-sectional survey conducted in the latter half of 2016. The study encompassed 18,506 women aged 15-49 with a history of at least one prior pregnancy. The primary outcome variable was the planning status of the most recent pregnancy, while the principal independent variable was unmet contraceptive need. Additional variables were controlled in the analysis. Data analysis was performed using STATA version 17, involving descriptive analysis, cross-tabulation, chi-square testing, and logistic regression. Statistical significance was set at p < 0.05. A substantial proportion of women reported unintended pregnancies (44.5%), with approximately 21.09% experiencing an unmet need for contraception. In the adjusted model, women with unmet contraceptive needs had 3.97 times higher odds of unintended pregnancy (95% CI = 3.61-4.37) compared to those with met contraceptive needs. Significant factors linked to unintended pregnancies included women's age, place of residence, household wealth status, decision-making authority regarding contraceptive use, educational attainment, husband's occupation, and educational level. This study revealed that both the rate of unintended pregnancies and unmet contraceptive needs in Uganda exceeded the global average, warranting urgent policy attention. Addressing unmet contraceptive needs emerges as a potential strategy to curtail unintended pregnancies. Further qualitative research may be necessary to elucidate the sociocultural and behavioral determinants of unwanted pregnancies, facilitating context-specific interventions.
Keywords: Unintended/Unwanted/Unplanned pregnancy, Reproductive health, Uganda, Unmet need for contraception